Rectal cancer management during the COVID-19 pandemic (ReCaP): multicentre prospective observational study. Issue 11 (7th May 2021) - Clifford, R E; Harji, D; Poynter, L; Jackson, R; Adams, R; Fearnhead, N S; Vimalachandran, D; ,
Abstract : Concerns over unacceptable high mortality in patients with rectal cancer undergoing surgery or systemic therapy who contract COVID-19 have led to widespread adoption of alternative treatment strategies.The ReCaP study aimed to study these variations and associated outcomes.